The Cyprus Issue: Reflection on TRNC - Biswas, Md Ataur Rahman (Arts Faculty Journal, 2012)
Cyprus is a Eurasian island country located in the Eastern Mediterranean Sea, east of Greece, south of Turkey, west of Syria and Lebanon and north of Egypt. Cyprus is the third largest island in the Mediterranean Sea. The earliest known human activity on the island dates back to around the 10th millennium BC. At a strategic location in the Middle East, Cyprus has been occupied by several major powers, including the empires of the Hittites, Assyrians, Egyptians, Persians, Rashidun and Umayyad Arab caliphates, Lusignans, Venetians, and Ottomans. Settled by Mycenean Greeks in the 2nd millennium BCE, the island also experienced long periods of Greek rule under the Ptolemaic Egyptians and the Byzantines. In 333 BC, Alexander the Great conquered the island from the Persians. The Ottoman Empire conquered the island in 1571 and it remained under Ottoman control for over three centuries. It was placed under British administration in 1878 until it was granted independence in 1960, becoming a member of the Commonwealth the following year. In this paper an attempt is made to discuss the details about the Turkish Republic of Northern Cyprus (TRNC) commonly called Northern Cyprus, which is a self-declared state that comprises the northeastern part of the island of Cyprus recognized only by Turkey and the problems associated with it. DOI: http://dx.doi.org/10.3329/afj.v4i0.12937 The Arts Faculty Journal Vol.4 July 2010-June 2011 pp.137-146